Toxoplasmosis: A Link To Mental Illness - IP Oladapo (Global Journal of Zoology - Peertechz Publications, 2020)
Toxoplasmosis is ubiquitous and capable of infecting virtually if not all mammalian species. Reports on latent toxoplasmosis have shown to affect one- third of the total population. The incidence of toxoplasmosis differs, however, with underdeveloped countries having a higher incidence than developed countries. While many people throughout the world are infected with Toxoplasma gondii and the prevalence of mental illness is rare in comparison, Toxoplasma gondii should at least be considered as contributing factor in mentally ill people who may have been exposed to Toxoplasma gondii. The CNS is mainly affected by toxoplasmosis, placing certain groups of individuals at higher risk over others. Toxoplasma gondii infection has been linked with psychiatric illnesses however, research on the causal pathway is limited and therefore not clearly developed. The aim of this review is to discuss the link between Toxoplasmosis and mental illness.